2014
DOI: 10.1016/j.carbon.2013.09.059
|View full text |Cite
|
Sign up to set email alerts
|

A new molecular model for water adsorption on graphitized carbon black

Abstract: Adsorption of water on graphitized carbon black at various temperatures has been studied with a new molecular model of graphitized carbon black using Monte Carlo simulation. The model is a collection of graphene layers, modelled by the Steele potential, and a number of phenol groups forming clusters of various sizes which are placed randomly at the graphene edge sites to give an O/C ratio of 0.006. The results are compared with experimental data reported by Kiselev et al. [1] in 1968 for a range of temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Thus it is concluded that water adsorbs on the functional groups at the junctions between adjacent graphene layers and argon adsorbs on the layers, and this is supported with our recent simulation work [20].…”
Section: Water Adsorption On Carbopack F and Hexsupporting
confidence: 74%
See 1 more Smart Citation
“…Thus it is concluded that water adsorbs on the functional groups at the junctions between adjacent graphene layers and argon adsorbs on the layers, and this is supported with our recent simulation work [20].…”
Section: Water Adsorption On Carbopack F and Hexsupporting
confidence: 74%
“…As the loading is increased water clusters are formed around the functional groups and grow in size because of the greater electrostatic interaction between water molecules than the dispersive water-graphene interaction [17]. This mechanism of adsorption was taken into account in the recent theories for water adsorption in porous carbon [12,18], and is also justified with molecular dynamics [19] and Monte Carlo simulations [20].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
“…Adsorption of water on carbon surfaces has been intensively studied [2,3], these materials presenting interesting environmental applications as adsorbents in aqueous solutions. In the graphitic form, carbon should not have strong interactions with water, since weak forces are involved in these interactions, but several simulations proved that water can be strongly adsorbed at low relative pressures by carbon adsorbents due to the potential overlap in small pores [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This also allows us to elucidate the mechanism of water adsorption: water molecules mainly cluster around the functional group, rather than on the basal plane, and once water has been adsorbed on the functional group, this complex acts as a nucleus for more water molecules to grow around it and form a larger cluster because the water-water intermolecular interaction is much greater than that between water and the basal plane. More details can be found in [48]. …”
mentioning
confidence: 99%